"After the End Times": Postcrisis African Science Fiction. (12th February 2014) - Omelsky, Matthew
<x content-type="archive" xml:space="preserve">Abstract</x> We live in a moment of "apocalyptic time, " the "time of the end of time." Ours is a moment of global ecological crisis, of the ever-impending collapse of capital. That we live on the brink is too clear. What is not, however, is our ability to imagine the moment after this dual crisis. In recent years, African artists have begun to articulate this "moment after, " ushering in a new paradigm in African literature and film that speculates upon postcrisis African futures. Writers and filmmakers such as Nigeria's Efe Okogu and Kenya's Wanuri Kahiu have imagined future African topographies—spaces that have felt the fullest effects of climate change, nuclear radiation, and the imbalances of global capitalism. Biopolitics, sovereignty, and the human have all been reconfigured in these African science fictions. Okogu and Kahiu's futurist aesthetics are specters that loom over our present, calling for a radically reimagined politics of the now.